Neuroticism and maladaptive coping in patients with functional somatic syndromes. Issue 4 (6th October 2016) - Frølund Pedersen, Heidi; Frostholm, Lisbeth; Søndergaard Jensen, Jens; Ørnbøl, Eva; Schröder, Andreas
Abstract : Objectives: The cognitive‐behavioural model of functional somatic syndromes (FSS) proposes a multifactorial aetiology consisting of predisposing, precipitating and perpetuating factors. In this study, we sought to investigate three questions that can be drawn from this model: (1) Do patients with FSS show high levels of neuroticism? (2) Does neuroticism affect physical health and social functioning, either directly or indirectly through maladaptive coping? (3) Does more adaptive coping mediate the effect of cognitive‐behavioural therapy (CBT) on outcome? Design: Secondary analysis of a randomized controlled trial (RCT) using additional data. Method: We used yet unpublished data on neuroticism (measured with Temperament and Character Inventory, Revised) and coping (measured with Coping Strategies Questionnaire) together with already reported outcomes (physical health and social functioning measured with SF‐36) from an RCT comparing group CBT with enhanced usual care in 120 patients with a range of FSS. Neuroticism was measured at referral, while coping and outcomes were measured at referral, baseline, 4 and 16 months after randomization. Our hypotheses were explored through a series of cross‐sectional (linear regression and structural equation models) and longitudinal (mediation) analyses. Results: Patients with FSS showed higher levels of neuroticism than two healthy comparison groups. At referral, symptom catastrophizing partly mediated the negative association between neuroticism and outcome. Reduction in symptom catastrophizing during group CBT partially mediated its long‐term effect. Conclusions: The results give support to a generic cognitive‐behavioural model of FSS. Targeting symptom catastrophizing may be an essential component in CBT for patients with FSS, regardless of their specific diagnosis. Statement of contribution What is already known on this subject? Previous studies have found support for single components of the cognitive‐behavioural model such as dysfunctional illness beliefs or avoidant coping. Most studies have investigated single functional somatic syndromes (FSS) such as fibromyalgia or irritable bowel syndrome. What does this study add? Predisposing neuroticism was linked to poor physical health through symptom catastrophizing across a range of FSS. Reduced symptom catastrophizing during group cognitive‐behavioural therapy partially mediated its long‐term effect. Addressing symptom catastrophizing may be a key element of the management of patients with FSS.